US state alcohol sales compared to survey data, 1993–2006 - David E. Nelson; Timothy S. Naimi; Robert D. Brewer; James F. Roeber (2010)
ABSTRACT Aims Assess long‐term trends of the correlation between alcohol sales data and survey data. Design Analyses of state alcohol consumption data from the US Alcohol Epidemiologic Data System based on sales, tax receipts or alcohol shipments. Cross‐sectional, state annual estimates of alcohol‐related measures for adults from the US Behavioral Risk Factor Surveillance System using telephone surveys. Setting United States. Participants State alcohol tax authorities, alcohol vendors, alcohol industry (sales data) and randomly selected adults aged ≥ 18 years 1993–2006 (survey data). Measurements State‐level per capita annual alcohol consumption estimates from sales data. Self‐reported alcohol consumption, current drinking, heavy drinking, binge drinking and alcohol‐impaired driving from surveys. Correlation coefficients were calculated using linear regression models. Findings State survey estimates of consumption accounted for a median of 22% to 32% of state sales data across years. Nevertheless, state consumption estimates from both sources were strongly correlated with annual r‐values ranging from 0.55–0.71. State sales data had moderate‐to‐strong correlations with survey estimates of current drinking, heavy drinking and binge drinking (range of r‐values across years: 0.57–0.65; 0.33–0.70 and 0.45–0.61, respectively), but a weaker correlation with alcohol‐impaired driving (range of r‐values: 0.24–0.56). There were no trends in the magnitude of correlation coefficients. Conclusions Although state surveys substantially underestimated alcohol consumption, the consistency of the strength of the association between sales consumption and survey data for most alcohol measures suggest both data sources continue to provide valuable information. These findings support and extend the distribution of consumption model and single distribution theory, suggesting that both sales and survey data are useful for monitoring population changes in alcohol use.